An in vitro study: prebiotic effects of edible palm hearts in batch human fecal fermentation system - Chai, Lee-Ling; Tan, Hui Yan; Saupi, Noorasmah; Saari Nazamid, Shahrul Razid (John Wiley and Sons, 2022)
BACKGROUND:Edible palm hearts (EPH), known as palmito, chonta or swamp cabbage in America or umbut in Malaysia, is a type of vegetable harvested from palm tree species. EPH is firm and smooth and described as having a flavor resembling artichoke. It has underlying prebiotic potential that selectively stimulates the growth and activity of beneficial colonic microbiota, thus enhancing the host's health. This study is the first to present results of EPH from local species such as oil palm (Elaeis guineensis), sago palm (Metroxylon sagu) and coconut (Cocos nucifera) using in vitro colonic fermentation with human fecal slurry. Samples obtained at 0, 6, 12 and 24 h were evaluated by bacterial enumeration using fluorescent in situ hybridization (FISH), and short-chain fatty acids (SCFA) were analyzed by high-performance liquid chromatography (HPLC). RESULTS: All EPH samples revealed induction effects towards Bifidobacterium spp., Lactobacillus–Enterococcus and Bacteroidaceae/Prevotellaceae populations similar to those in inulin fermentation. A significant decrease (P ≤ 0.05) in pathogenic Clostridium histolyticum group was observed in the response of raw sago palm hearts. In general, all samples stimulate the production of SCFA. Particularly in the colonic fermentation of sago palm heart, acetate and propionate revealed the highest concentrations of 286.18 and 284.83 mmol L−1 in raw and cooked form, respectively. CONCLUSION: This study concluded that edible palm hearts can be a potential prebiotic ingredient that promotes human gastrointestinal health, as well as discovering a new direction towards an alternative source of functional foods.